2016
DOI: 10.1007/s13224-016-0861-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Use of Long-Term, Low-Dose Mifepristone for the Treatment of Fibroids

Abstract: Background Fibroid or myoma is the commonest reported tumor of uterus, and is one of the important reasons for hysterectomy in our setting. Different drugs are available for medical management of fibroid uterus including mifepristone, a progesterone antagonist. Varying dosage regimen for mifepristone was studied as medical management of fibroid uterus. The aim of the project was to study the effect of mifepristone on the symptoms and size of fibroids, especially using a low-dose regimen for 6 months. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
(9 reference statements)
1
10
0
3
Order By: Relevance
“…Recently, different administration schedules were evaluated in two Indian trials, using weekly or biweekly doses of 50 mg claiming good results 126,127. Using the vaginal route for the administration of 10 mg daily of MFP, treatment significantly reduced the volume of fibroids 128…”
Section: Selective Progesterone Receptor Modulators (Sprms)mentioning
confidence: 99%
“…Recently, different administration schedules were evaluated in two Indian trials, using weekly or biweekly doses of 50 mg claiming good results 126,127. Using the vaginal route for the administration of 10 mg daily of MFP, treatment significantly reduced the volume of fibroids 128…”
Section: Selective Progesterone Receptor Modulators (Sprms)mentioning
confidence: 99%
“…The study showed that after 6 months of therapy, the fibroid volume reduced by 44.57% and bleeding per vaginam decreased by 100%. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Although hysterectomy is the definitive treatment, myomectomy is an alternative for those who desire to preserve their uterus, and medical approaches are also of great interest. 41,44 Several pieces of evidence indicate that progesterone may be involved in the pathogenesis of leiomyoma, making antiprogestins, such as mifepristone, an attractive therapeutic option. 43 Various dosages of mifepristone have been used in different studies, and 10-20 mg/d seems to provide the most benefit, and higher doses increased the risk of adverse effects, such as hot flushes, elevated aspartate aminotransferase and alanine aminotransferase levels, endometrial hyperplasia, and antiglucocorticoid effects.…”
Section: Uterine Leiomyomamentioning
confidence: 99%